Engrailed controls the organization of the ventral nerve cord through frazzled regulation. - Joly, W.; Mugat, B.; Maschat, F. (Developmental Biology, 2007)
In Drosophila, the ventral nerve cord (VNC) architecture is built from neuroblasts that are specified during embryonic development, mainly by transcription factors. Here we show that Engrailed, a homeodomain transcription factor known to be involved in the establishment of neuroblast identity, is also directly implicated in the regulation of axonal guidance cues. Posterior commissures (PC) are missing in engrailed mutant embryos, and axonal pathfinding defects are observed when Engrailed is ectopically expressed at early stages, prior to neuronal specification. We also show that frazzled, enabled, and trio, all of which are potential direct targets of Engrailed and are involved in axonal navigation, interact genetically with engrailed to form posterior commissures in the developing VNC. The regulation of frazzled expression in engrailed-expressing neuroblasts contributes significantly to the formation of the posterior commissures by acting on axon growth. Finally, we identified a small genomic fragment within intron 1 of frazzled that can mediate activation by Engrailed in vivo when fused to a GFP reporter. These results indicate that Engrailed's function during the segregation of the neuroblasts is crucial for regulating different actors that are later involved in axon guidance.